2012
DOI: 10.1111/j.1399-3038.2012.01341.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral food desensitization in children with IgE‐mediated hen’s egg allergy: a new protocol with raw hen’s egg

Abstract: To cite this article: Meglio P, Giampietro PG, Carello R, Gabriele I, Avitabile S, Galli E. Oral food desensitization in children with IgE‐mediated hen’s egg allergy: a new protocol with raw hen’s egg. Pediatr Allergy Immunol 2012: 00. Abstract Background:  Hen’s egg allergy affects young children and can cause severe allergic reactions. Avoidance results in dietary limitations and can affect the quality of life, especially in cases where potentially life‐threatening reactions exist. Our objective was to desen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
132
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(142 citation statements)
references
References 30 publications
7
132
2
1
Order By: Relevance
“…Nurmatov et al reported that OIT can promote allergen desensitization, but the risk of local adverse reactions increased with OIT in a metaanalysis (4). Failure of OIT, in which allergen desensitization was not achieved, has also been reported (16,31). In this experiment, the allergic response and some allergy biomarkers in the OIT-treated mice were found to be worse than those of the non-treated mice.…”
Section: Discussionmentioning
confidence: 58%
“…Nurmatov et al reported that OIT can promote allergen desensitization, but the risk of local adverse reactions increased with OIT in a metaanalysis (4). Failure of OIT, in which allergen desensitization was not achieved, has also been reported (16,31). In this experiment, the allergic response and some allergy biomarkers in the OIT-treated mice were found to be worse than those of the non-treated mice.…”
Section: Discussionmentioning
confidence: 58%
“…Other studies of egg OIT included the small RCTs by Dello Iacono et al and Meglio et al, who reported desensitization rates of 80%-90% in children with severe egg allergy, and 2 studies using rush protocols with desensitization induced in as few as 5 days [32][33][34][35].…”
Section: Egg Oitmentioning
confidence: 99%
“…This appears particularly suitable for cow's milk (CM), hen's egg (HE), and peanut allergies. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Several clinical studies on the oral administration of allergy foods are available, and some trials are currently under way to better define indications, contraindications, and practical aspects. Of note, there is no specific study for non-IgE-mediated food allergy, such as food proteininduced enterocolitis syndrome.…”
mentioning
confidence: 99%